Access to a car in the cities of Sub-Saharan Africa: car use and car users in Dakar - (:unkn) unknown (My University, 2020)
Access to a car in the cities of Sub-Saharan Africa: car use and car users in DakarSub-Saharan Africa, which was home to 13 % of the world’s population in 2015, accounted for only 2 % of the car fleet at that date and private motorized transport is still at a very low level in many cities. Even though in recent years there has been genuine growth in the number of cars in African countries, mainly in the capitals and other large cities, the current size of fleets suggests that motor vehicle ownership and car use are still an unattainable dream for the majority of people. What is the situation in reality?This paper examines the place of the car through a study of its uses and its users in Dakar (Senegal): who owns one, who can use one, for what purposes and for what mobility practices, and how is the situation changing? We apply categorisation that distinguishes between three types of users, depending on whether or not their household owns a car and, if so, on their ability to access it at all times. Secondary analyses of two household mobility surveys carried out in Dakar in 2000 and 2015 and semi-directive interviews with residents of the city conducted in 2015 show that the concentration of car ownership has increased over the past fifteen years. The wealthiest households own proportionally more vehicles and the department of Dakar increased its share of vehicles compared to the other departments of metropolitan Dakar. The profiles of car users and their car use reveal that despite its scarcity and high cost of use, the car has spread beyond the select circle of city dwellers who have access to one at all times. But the three types of users are in situations of inequality with regard to the car. A comparison between 2000 and 2015 suggests future developments, driven by generational effects and spatial dynamics.
Keywords: African Research